SARS-CoV-2 in Pregnancy: Fitting Into the Existing Viral Repertoire - Rajput, Roopali; Sharma, Jitender (Frontiers in Global Women's Health, 2021)
The risk to viral infections during pregnancy is well-documented, however, limited understanding and restricted intervention modalities are in practice to enable maternal-fetal protection. This becomes all the more challenging during pandemics. During many different epidemic and pandemic viral outbreaks, the worse outcomes (fetal abnormalities, mortality, preterm labor, etc.) in pregnant women has been evident when compared to the non-pregnant counterparts. The condition of pregnancy, which is widely understood as “immunosuppressed” needs to be re-understood in terms of the way the immune system works during such state. The immune system gets transformed to accommodate and facilitate the fetal growth. The interference of such supportive conversion by viral infection and risk of co-infections leads to adverse fetal outcomes. Hence, it is crucial to understand the risk and impact of potent viral infections likely to be encountered during pregnancy. In the present article, we review the effects imposed by previously established and recently emerging/re-emerging viral infections on maternal and fetal health. Such understanding is important in devising strategies for better preparedness and knowing the treatment options to mitigate the relevant adverse outcomes.